2017
DOI: 10.3389/fnagi.2017.00299
|View full text |Cite
|
Sign up to set email alerts
|

A 58-Year Old Male with Cognitive Deteriorations Caused by Septum Pellucidum Cyst: A Case Report

Abstract: Dementia is known to be induced by vascular dementia and certain neurodegenerative diseases. The presenting features of disordered memory, intellect and personality often result in referral to a neurologist initially. Septum pellucidum cyst (SPC) is a rare clinical finding and defined as a cystic structure between the lateral ventricles. SPC induced memory disorder and dementia has been seldom reported in which the clinical features are atypical and can be misdiagnosed. The main difficulty is to establish a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The reported elderly cases of symptomatic SPCs, including the case described here, are shown in Table 1. 6,[12][13][14] Majority of the patients aged above 50 years complained of gait disturbance (about 67%). On the other hand, the reported cases, except the case presented here, complained of headache that might be related to high intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The reported elderly cases of symptomatic SPCs, including the case described here, are shown in Table 1. 6,[12][13][14] Majority of the patients aged above 50 years complained of gait disturbance (about 67%). On the other hand, the reported cases, except the case presented here, complained of headache that might be related to high intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that disconnection of the pathway between the diagonal band of Broca and the hippocampus contributed to declarative memory impairment ( Abe et al, 1998 ). A patient with a rare septum pellucidum cyst presented with memory impairment, an MRI scan showed that the cyst was limited to the septal region ( Chen et al, 2017 ). Mini-Mental State Exam (MMSE) and Montreal Cognitive Assessment (MoCA) revealed mild cognitive impairment before the treatment of the cyst.…”
Section: Mnemonic Medial Septummentioning
confidence: 99%
“…After neuroendoscopic fenestration of the cyst, the patient’s memory has improved. The authors concluded that the patient’s episodic memory disorder was due to a secondary septal lesion attributed to the cyst ( Chen et al, 2017 ). Studies in healthy participants extended the focus of septal contribution to memory formation.…”
Section: Mnemonic Medial Septummentioning
confidence: 99%